The Role of Islamic Education Teachers in Addressing the Negative Impact of the TikTok on Teenagers in Lampung, Indonesia - Sagala, Rumadani; Kandedes, Iin (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
This study investigated the role of Islamic education teachers in mitigating the negative impacts of TikTok on teenagers in Lampung, Indonesia. This study aimed to assess the extent of TikTok usage among teenagers, identify the associated negative effects, and analyze the strategies employed by Islamic religious education teachers to address these issues. This field study employed a qualitative case study approach, with a sample consisting of 455 adolescents (both male and female) aged 12 to 18 years, and 35 Islamic education teachers who actively participated in the intervention. Data collection was conducted in three stages: observation, interviews, and document analysis. Questionnaires and instruments were designed, and data obtained from Islamic education teachers were analyzed using the Miles and Huberman theoretical framework. The findings revealed that TikTok has a significant negative impact on adolescents, manifesting in various detrimental outcomes. Islamic religious education teachers have already implemented numerous roles and solutions to combat these issues, highlighting the necessity of a comprehensive and serious approach to address this problem. This study underscores the importance of empowering adolescents to resist the risks associated with the unwise and morally harmful use of TikTok, thus protecting their ethical development and well-being.